2015
DOI: 10.1017/s0266462315000732
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Principles for Good Practices in Hospital-Based Health Technology Assessment Units

Abstract: Guiding principles for good practices set up a benchmark for HB-HTA because they represent the ideal performance of HB-HTA units; nevertheless, when performing HTA at hospital level, context also matters; therefore, they should be adapted to ensure their applicability in the local context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 28 publications
0
40
0
9
Order By: Relevance
“…Thus, local HTA models have been set up in hospitals for the purchasing of health technologies including drug therapies, equipment, and medical devices (MDs). This approach considers a wide range of aspects, including the medical, social, ethical, and economic implications of the development, diffusion, and use of health technologies . Several authors highlight that, to capture their overall impact, nonclinical criteria must be integrated into the assessment of MDs .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, local HTA models have been set up in hospitals for the purchasing of health technologies including drug therapies, equipment, and medical devices (MDs). This approach considers a wide range of aspects, including the medical, social, ethical, and economic implications of the development, diffusion, and use of health technologies . Several authors highlight that, to capture their overall impact, nonclinical criteria must be integrated into the assessment of MDs .…”
Section: Introductionmentioning
confidence: 99%
“…Tal estágio de evolução permitiu que houvesse experiência e massa crítica suficientes para o desenvolvimento de amplo estudo sobre boas práticas de ATS em hospitais. Sampietro-Colom et al (2016) realizaram estudo para a definição de princípios de boas práticas de ATS em hospitais. O estudo foi conduzido por especialistas europeus que realizaram um amplo trabalho envolvendo revisão de literatura, pesquisas em larga escala, grupo focal, pesquisa Delphi e mais de cem entrevistas presenciais.…”
Section: Boas Práticas Em Atsunclassified
“…De acordo com os autores, os resultados do trabalho da unidade de ATS em hospitais devem ser medidos pelo impacto interno e externo, a curto e médio prazos, bem como o impacto a longo prazo no desempenho do hospital e na saúde das comunidades. Foram definidos 15 princípios orientadores para boas práticas de ATS em hospitais, os quais estão organizados em quatro diferentes dimensões: Processo de Avaliação; Liderança, Estratégia e Parcerias; Recursos; e Impacto (Sampietro-Colom et al, 2016).…”
Section: Boas Práticas Em Atsunclassified
“…Literature states that POS could support the continuous learning development of any healthcare organisation, fostering innovation processes [19,22]. Research [23] has revealed the capability of POS to assist and sustain healthcare decision-makers in the formal redesign and evaluation of patient processes, thus optimising their clinical pathway, achieving a higher efficiency, and leveraging exploitation activities. Therefore, POS is strategically relevant in hospital settings, being related to the quality of results achieved, spending less time for their achievement [19], and impacting hospital policies [24].…”
Section: Perceived Organisational Supportmentioning
confidence: 99%